Dynamic analysis of holographic gratings in a multi-wavelength visible light sensitive photopolymer - 陈珂 成建群 王艳 黄明举 (Chinese physics B, 2010)
A dynamic theoretical model of photochemistry and hologram formation in holographic photopolymer is established, and the dynamic development process of holographic gratings in the photopolymer is discussed with the model. A novel multi-wavelength visible light sensitive photopolymer for holographic storage is prepared. The influence of exposure wavelength on holographic storage characteristics is analysed. By fitting the experimental data of transmittance and diffraction efficiency to a function of time with different exposure intensities and wavelengths, the variations of dynamic parameters of photochemistry and photopolymerization diffusion are presented.